2000
DOI: 10.4049/jimmunol.164.9.4672
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 Receptor Independent Stimulation of Human gp130 by Viral IL-6

Abstract: The genome of human herpes virus 8, which is associated with Kaposi’s sarcoma, encodes proteins with similarities to cytokines and chemokines including a homologue of IL-6. Although the function of these viral proteins is unclear, they might have the potential to modulate the immune system. For viral IL-6 (vIL-6), it has been demonstrated that it stimulates IL-6-dependent cells, indicating that the IL-6R system is used. IL-6 binds to IL-6R, and the IL-6/IL-6R complex associates with gp130 which dimerizes and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
83
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 40 publications
3
83
0
1
Order By: Relevance
“…After stable transfection of a cDNA coding for gp130, these cells (Ba/F3-gp130), in the absence of IL-3, gain the ability to proliferate in the presence of IL-6/sIL-6-R, hyper-IL-6 (a fusion protein of IL-6 and sIL-6-R) (21), or viral IL-6. Previous studies have shown that Ba/F3-gp130 cells proliferate in response to hyper-IL-6 at a concentration below 1 ng/ml, whereas 100 ng/ml of viral IL-6 was needed to induce Baf/3-gp130 cell proliferation (26,46).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After stable transfection of a cDNA coding for gp130, these cells (Ba/F3-gp130), in the absence of IL-3, gain the ability to proliferate in the presence of IL-6/sIL-6-R, hyper-IL-6 (a fusion protein of IL-6 and sIL-6-R) (21), or viral IL-6. Previous studies have shown that Ba/F3-gp130 cells proliferate in response to hyper-IL-6 at a concentration below 1 ng/ml, whereas 100 ng/ml of viral IL-6 was needed to induce Baf/3-gp130 cell proliferation (26,46).…”
Section: Resultsmentioning
confidence: 99%
“…COS-7 and HepG2 cells were bought from the ATCC (Rockville, MD) and were routinely grown in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% fetal calf serum (FCS). The vIL-6 DNA sequence was originally obtained from F. Neipel and B. Fleckenstein (University of Erlangen, Germany) (48) and has been used in previous studies (26,46). The PEL-derived BCBL-1 cells were a kind gift from M. Gramatzki's group at the University of Kiel (Germany) and were maintained in RPMI 1640 medium (BioWhittaker,Walkersville, MD) supplemented with 2 mmol/liter L-glutamine (Life Technologies, Grand Island, NY), 10% fetal calf serum (BioWhittaker), and 5 g/ml gentamicin (Life Technologies).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations